At risk alcohol consumption with smoking by national background: Results from the Hispanic community health study/study of Latinos. (December 2019) - Bandiera, Frank C.; Pérez-Stable, Eliseo J.; Atem, Folefac; Caetano, Raul; Vidot, Denise C.; Gellman, Marc D.; Navas-Nacher, Elena L.; Cai, Jianwen; Talavera, Gregory; Schneiderman, Neil; Kaplan, Robert
Abstract: Introduction: Tobacco smoking and binge or excess drinking are unhealthy behaviors that frequently co-occur. Studies of Hispanics/Latinos have mostly been of Mexican Americans although there are substantial differences in smoking and drinking by heritage background. Associated with co-use by 5 subpopulations. Methods: Cross-sectional data of 16, 412 Hispanics/Latinos from Miami, the Bronx, Chicago and San Diego collected between 2008 and 2011 as part of the HCHS/SOL were analyzed. Smoking and alcohol consumption and demographic data were measured by self-report. Prevalence of smoking and alcohol consumption and co-use were reported. Logistic regression models examined the odds of co-use of smoking and binge or excess alcohol use by Hispanic/Latino background group. Results: Men of Cuban (10.3%), Puerto Rican (8.9%), and Mexican (8.9%) background had the highest prevalence of co-use of smoking and binge drinking compared to men of Central American (6.1%) and Dominican (6.6%) background. Women of Dominican (16.4%) and Puerto Rican (19.7%) background had the highest prevalence of binge drinking compared to women of Central American (10%) and Cuban (8%) background and Puerto Rican (34.1%) and Cuban (21.8%) women were the most likely to report current smoking compared to women of Central American (8.3%) and Mexican (10.4%) background. Acculturation was not associated with co-use among men and women. Elevated depressive symptoms were positively associated with smoking and binge drinking among men, OR = 1.5 [1.2–2.0], and women, OR = 1.5 [1.1–2.2]. Puerto Rican women had increased odds of co-use of smoking and binge or excess drinking compared to Mexican American women, OR = 3.2 [1.5–6.6]. Conclusions: Puerto Rican and Dominican Latinas and Central American and South American men have a higher prevalence of co-use. Highlights: Caribbean Latinas were more likely to smoke and binge drink. Central and South American men were more likely to co-use. Acculturation was not positively associated with co-use of at-risk drinking and smoking.